Multifunctionality and Impacts of Organic and Conventional Agriculture - Moudrý, Jan; Ferreira Mendes, Kassio; Bernas, Jaroslav; da Silva Teixeira, Rafael; Nogueira de Sousa, Rodrigo (IntechOpen, 2020)
Organic farming aims to produce a number of crops, without the use of synthetic chemicals (pesticides) or fertilizers, while enhancing soil composition and promoting biodiversity. This is a traditional, more permanent type of farming that relies on ecosystem services to maintain the integrity of the landscape while still producing sufficient yields. In addition, conventional farming uses pesticides and fertilizers to maximize the yield of a particular crop or set of crops, which are typically genetically modified. This book covers several issues related to the multi-functionality and impacts of organic and conventional farming systems. Chapters cover topics related to organic farming and the economy, farm management, and innovative methods and approaches.